The effect of tropical land use change on soil-dwelling ants and termites, their interaction and on ecosystem processes they affect - Tůma, Jiří (Jihočeská univerzita, 2020)
In this thesis I explore the role of tropical soil-dwelling ants and termites in driving ecosystem processes, their mutual interaction and their responses to tropical land use change. To do this I use a combination of methods, including a full review of the ant-termite interaction literature, field sampling for ants and termites, DNA barcoding-based inference of ant predation on termites, and creation and implementation of a new protocol for measuring terrestrial bioturbation. I found that the literature mainly documents anecdotal observations of interactions between ants and termites, the vast majority of which are predatory. Many of these appear to be opportunistic predation of termites by non-specific ants, although some ant species have developed sophisticated methods that enable them to specialise on termite predation. My field sampling demonstrated that soil ants and termites are susceptible to habitat degradation, with logging having minimal impacts, but conversion to oil palm affecting both groups to a greater extent. The predation rate of ants on termites differs between ant taxa, but seems to be stable across habitats. Finally, termites are important for soil bioturbation in all habitat types, but overall, this ecosystem function relies only on few species in oil palm plantations, raising concerns about susceptibility of this function to future extinctions. My work emphasizes the importance of maintaining the diversity of these two trophically linked groups for the ecosystem functions they provide.
The effect of tropical land use change on soil-dwelling ants and termites, their interaction and on ecosystem processes they affect
Keywords: land use; ants; termites; interaction; tropical habitats; soil; oil palm; bioturbation; land use; ants; termites; interaction; tropical habitats; soil; oil palm; bioturbation